Segregation Analyses of Partial Self-Incompatibility in Self and Cross Progeny of Solanum carolinense Reveal a Leaky S-Allele - Mena-Ali, Jorge I. (Copyright © 2007 by the Genetics Society of America, 2007)
Natural populations of self-incompatible species often exhibit marked phenotypic variation among individuals in the strength of self-incompatibility (SI). In previous studies, we found that the strength of the SI response in Solanum carolinense, a weedy invasive with RNase-mediated SI, is a plastic trait. Selfing can be particularly important for weeds and other successional species that typically undergo repeated colonization and local extinction events and whose population sizes are often small. We applied a PCR-based protocol to identify the S-alleles present in 16 maternal genotypes and their offspring and performed a two-generation greenhouse study to determine whether variation in the strength of SI is due to the existence of weak and strong S-alleles differing in their ability to recognize and reject self-pollen. We found that allele S(9) sets significantly more self seed than the other S-alleles in the population we sampled and that its ability to self is not dependent on interactions with other S-alleles. Our data suggest that the observed variations in self-fertility are likely due to factors that directly influence the expression of SI by altering the translation, turnover, or activity of the S-RNase. The variability in the strength of SI among individuals that we have observed in this and our previous studies raises the possibility that plasticity in the strength of SI in S. carolinense may play a role in the colonization and establishment of this weedy species.